Patina - Reynolds, Jason (New York : Atheneum Books for Young Readers, 2017)
A newbie to the track team, Patina "Patty" Jones must learn to rely on her family and teammates as she tries to outrun her personal demons.
Booklist starred, August 2017
Kirkus Starred, July 2017
New York Times, August 2017
4.6
5-8
710L
Keywords: Track and field -- Fiction; Stress (Physiology) -- Fiction; Family problems -- Fiction; Diabetes -- Fiction; African Americans -- Fiction; Running -- Fiction; Track athletics -- Fiction; Stress (Physiology) -- Fiction; Family life -- Fiction; Diabetes -- Fiction; African Americans -- Fiction